Implementation of Microsoft Excel-Based Accounting System in Financial Recording in MSMEs - Jovianto, Jovianto; Harsono, Budi (ConCEPt - Conference on Community Engagement Project, 2025)
In this community service activity, the activity are implementation to a business that is mirco small medium enterprise (MSME) that named Oleh-Oleh ABC. In MSME Oleh-Oleh ABC, they are selling Batam food souvenirs, such as curry puff and other, where also some food souvenirs are hand made by the owner. In the MSME Oleh-Oleh ABC, owner are lacks a system or a software that can assist MSME in automatically helping to recording transactions and also calculating finansial report. Therefore the goal of this activity is helping MSME to create a system that based by microsoft excel that with macor capabilities, so that will assist MSME in recording transaction and calculating transactions. With this software system the owner will easy and less errors while recording transaction, calculating, and preparing finansial reports. The implementation method for this activity is the development of appropriate technology. Students visit MSMEs to understand their situation and needs. Afterward, they develop a software system that can adapt to user needs. Recommendations for further community service activities are that students can use other software systems for MSME users, or students can add several features or formulas that are not available in this Microsoft Excel-based software system.